Влияние ДДТ и хлорофоса на генеративную функцию зайца-русака (Lepus europaeus Pallas, 1778) - Шевченко, Л.С. (Вестник зоологии, 1969)
Seven individuals of Lepus europaeus Pallas were fed with 0.8 g dichlorodiphenyl trichloroethane per 1 kg of food during ten days. Four animals died. A strong distrubance in the structure and function of gonads was observed in the animals of this series of experiments. When feeding the hares with 0.3 g of DDT per t kg of food the death of animals was not observed. The gonads were less affected than in the first experiment. However the data of morphological and hormonal investigations testify to high sensitivity of the generative system (especially that of males) to DDT. Dimethyl-2, 2. 2-trichloroxyethylphosphate fed in the same doses as DDT did not cause considerable changes in the general state of the organism and in the generative system of the animals under experiment.